Madrasah Berprestasi: Analisis Visi, Program, dan Strategi Kepemimpinan Kepala Sekolah di Man 1 Lombok Timur: Penelitian - Hasrul Hadi; Muh Fikron Birrulwalidain; Muliyana; Anggraeni; Zuryati Paziah; Nadia Nurliza Marzuki (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
Although the leadership of school principals has been widely researched, specific studies analyzing how the vision, programs, and leadership strategies are integrated within madrasah (Islamic schools) still a little. This research aims to evaluate the vision, flagship programs, and leadership strategies of the school principal at MAN 1 East Lombok. The method used is a descriptive qualitative approach with a case study design, involving the principal, teachers, and students selected through purposive sampling. Data was collected through interviews, observation, and documentation analysis, and then analyzed using the Miles and Huberman interactive model. The research findings indicate that the success of MAN 1 East Lombok is supported by three main strategies: transparent financial management, attention to student activities, and provision of appreciation for outstanding teachers and students. These results support the theory of transformational leadership within the context of Islamic education and affirm the importance of harmony between vision, programs, and strategies in creating a superior and competitive madrasah.